Microstructural Evaluation of an Austempered Cast Iron Alloy - Pereira,Letyssia Niara De Godoi (2022)
Abstract ADI are the result of graphite nodules and ausferrite microstructure (acicular ferrite + retained austenite). Over the past few years, ADI has become an important material for engineering due to its excellent mechanical properties (outstanding ductility, high mechanical strength and good toughness) and low cost. It is known the discussion of process variables such as austempering time and temperature are extremely important for the microstructural and hardness study of these materials. Thus, in the present work, ADI cast iron was investigated under twelve different austenitic conditions, aiming to characterize the influence of the amount of austenite on the ferritic matrix on the mechanical property of hardness. The heat treatment parameters vary from three different times (40 min, 90 min and 180 min) under four temperatures (280ºC, 300 ºC, 320 ºC and 370ºC). Results show there is a decreasing of hardness linked to the increasing of retained austenite % volume. The greater amount of retained austenite % volume in the matrix was presented by sample A14, treated during 40 minutes under 370ºC and presenting 32.30% of this microconstituint. The amounts of each phase present in the studied materials were raised by quantitative metallography through the software Fiji-ImageJ, allowing a comparison of the results obtained by these two methods. Time differences on the austempering heating treatment did not show several implications on ADI microstructure. In addition, analyzes of the graphite nodules were performed.